PERENCANAAN DAN PERANCANGAN SENTRA KOPI ARABIKA DI KINTAMANI: Bahasa Indonesia - Putu Julianita Dewi; I Nyoman Nuri Arthana; Made Anggita Wahyudi Linggasani; Made Arya Adiartha (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2026)
Kintamani is a highland area in Bangli Regency, Bali, which has great potential in the production of high-quality Arabica coffee and the development of agriculture-based tourism. However, coffee production, education, and tourism activities in this area are still carried out separately so that the added value and welfare of farmers are not optimal. This study aims to design the Arabica Coffee Center in Kintamani as an integrated area that integrates the functions of production, education, training, tourism, and sustainable environmental management. The method used is a qualitative method with a descriptive-analytical approach through literature studies, field observations, interviews, and data analysis as the basis for formulating the design concept. The design approach carries the Integrated & Experiential concept with the theme of Neo-Vernacular Architecture that adapts local cultural values, natural conditions, and modern technology. The design results in a coffee center area that has integrated functions, a clear flow of activities, and educational and recreational space experiences, with an efficient structural system and contextual architectural expression. The Arabica Coffee Center in Kintamani is expected to strengthen the identity of local coffee, improve the quality of processing and education, support the community's economy, and maintain the sustainability of the area's environment.